Development of cement kiln dust (CKD) based catalyst for biodiesel production from waste cooking oil - Nuruljannah, Samidi (2012)
Cement kiln dust(CKD)is alkaline materials which produce as a by-side product in the cement manufacturing process which contain amount of alkalis like NA2O,K2O and large amount of free lime.The price of catalyst derived from noble metals such as platinum is expensive and this will drive the price of biodiesel even higher than the dinodiesel. Therefore, it is necessary to synthesize a cheaper catalyst to make the production of biodiesel competitive and feasible.In this work,CKD will be utilised as raw material to produce catalyst for transesterification of waste cooking oil.This CKD based catalyst was prepared by impregnated with the potassium hydroxide and the other by methanol and water.The catalyst was calcined at 650 °C for 3 hours.The transesterification process of waste cooking oil with methanol was used to investigate the yield of biodiesel. The catalysts were characterized using pH measurement, Thermogravimetric analysis(TGA)and Fourier transform infrared (FTIR). The experimental result showed that a CKD/KOH give the highest purity and yield of biodiesel compared to the other catalyst which is 97.85% and 89.34%. The higher alkalinity gives the higher purity and yield. This CK/KOH catalyst is the best catalyst compared to CKD, CKD/CH3OH and CKD/H2O for the biodiesel production. The catalyst can be produce with a low cost of material and high efficiency of production.